2006
DOI: 10.1159/000096278
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genetics into Advanced Practice Nursing Curriculum: Strategies for Success

Abstract: Keeping up with the volume of new genetic information emerging from the human genome project is a challenge for almost all healthcare providers, but nurses who received little or no formal genetic training often find it particularly intimidating. Nursing faculty may be reluctant to add genetic content to existing courses, much less tackle the work of teaching an entire course in genetics. This article provides nursing faculty with some strategies and straightforward curriculum modifications to assist them in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Similarly, Sobhy et al found that nursing students who are well informed about genetic counselling services are better informed about genetic education and can provide genomics education to their patients [13]. The research findings emphasize the importance and urgency of education that focuses on both prenatal genetics and screening [12].…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Sobhy et al found that nursing students who are well informed about genetic counselling services are better informed about genetic education and can provide genomics education to their patients [13]. The research findings emphasize the importance and urgency of education that focuses on both prenatal genetics and screening [12].…”
Section: Discussionmentioning
confidence: 84%
“…This is the future of the nursing profession and these are the essential elements for a 21st century nurse. The goal to increase genetic and genomic understanding, awareness and appreciation [24] is the requirement of all nurse educators, nurses and healthcare providers. As such, the nursing profession, as a whole, must be prepared to be active participants with effective roles in genetic and genomic healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…Education which focuses on increasing nursing awareness of the significance of genomics and enables students to acquire a basic understanding of the impact of genetics and genomics on clinical practice can provide an important foundation for further genomics education [43]. However, nursing faculties may be reluctant to add genetics to existing courses, let alone tackle the work of teaching an entire course in genetics [44].…”
Section: Discussionmentioning
confidence: 99%